2009
DOI: 10.1021/es802030k
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Interactions of EDDS with Soils. 1. Metal Resorption and Competition under EDDS Deficiency

Abstract: Biodegradable EDDS ([S,S]-ethylenediaminedisuccinic acid) is an emerging chelant for enhancing heavy metal extraction. During soil remediation that involves continuous flushing, metal extraction is often limited by the amount of EDDS. Under EDDS deficiency, initial extraction of Zn and Pb followed by resorption was observed in batch kinetic experiments. Speciation calculations indicated that the percentages of ZnEDDS(2-) and PbEDDS(2-) in respective dissolved metal concentrations decreased with time, whereas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 43 publications
4
26
0
Order By: Relevance
“…The former can directly break down some weak bonds between metals and soils, while the latter can indirectly mobilize metals that are bound to oxides and organic matter through partially disrupting the soil structure. In aged contaminated sites, the majority of the metal species are bound to oxides or organic matter, EDTA-promoted dissolution can play a substantial role in the overall metal removal under the chelator adequacy [24]. EDTA-promoted dissolution itself also includes two steps: a fast adsorption of free or complexed EDTA onto specific surface sites via surface complexation, which can destabilize the metal-oxygen bonds in mineral structure, followed by a rate-limiting metal detachment from the oxide structure.…”
Section: Introductionmentioning
confidence: 99%
“…The former can directly break down some weak bonds between metals and soils, while the latter can indirectly mobilize metals that are bound to oxides and organic matter through partially disrupting the soil structure. In aged contaminated sites, the majority of the metal species are bound to oxides or organic matter, EDTA-promoted dissolution can play a substantial role in the overall metal removal under the chelator adequacy [24]. EDTA-promoted dissolution itself also includes two steps: a fast adsorption of free or complexed EDTA onto specific surface sites via surface complexation, which can destabilize the metal-oxygen bonds in mineral structure, followed by a rate-limiting metal detachment from the oxide structure.…”
Section: Introductionmentioning
confidence: 99%
“…For example, facilitating agents such as surfactants, cosolvent and cyclodextrins can enhance the washing of HOCs from soils and sediments (Sheremata and Hawari, 2000;Yang et al, 2006, Yuan et al, 2007aWang and Keller, 2008;Han et al, 2009), and complexants are effective to increase the washing of heavy metals (Yuan et al, 2007b, Koopmans et al, 2008Udovic and Lestan, 2009;Yip et al, 2009). However, it is still difficult to reach efficient simultaneous washing of HOCs and heavy metals from soils and sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6 illustrates a nonlinear relationship between the values of k′ and the required time, in which a slower metal extraction presented a greater dependence on the extraction rates. By contrast, the variations of k″ values resulted in mixed effects; Pb extraction was negligibly affected, Cu extraction was nonlinearly correlated, and Zn extraction showed an inverse relationship because of its negative k 3 ″ value (see Table 2) resulting from metal exchange and readsorption (Tsang et al 2009;Yip et al 2009a). In addition, it is noted that at the lowest k′ values or the highest k ″ values, the metal extraction kinetics (see Figs.…”
Section: Significance Of F K′ and K″mentioning
confidence: 99%
“…Recent results further indicated that there were relationships between the initial metal distribution in soils and the amounts of readily extractable, less extractable, and non-extractable metals (Fangueiro et al 2005) and that the extraction kinetics were not the same in different fractions (Wasay et al 2007;Yip et al 2009a). For a better description of the extraction kinetics, the time-dependent metal extraction could be operationally defined into two stages: fast extraction that takes place within 2 h and slow extraction that continues beyond 2 h (Bermond and Ghestem 2001;Fangueiro et al 2002).…”
Section: Model Formulationmentioning
confidence: 99%
See 1 more Smart Citation